Interferon Regulatory Factor 4 Regulates the Development of Polymorphonuclear Myeloid-Derived Suppressor Cells Through the Transcription of c-Myc in Cancer - Yang, Quan; Xie, Hongyan; Li, Xing; Feng, Yuanfa; Xie, Shihao; Qu, Jiale; Xie, Anqi; Zhu, Yiqiang; Zhou, Lu; Yang, Jinxue; Hu, Xiaohao; Wei, Haixia; et al. (Frontiers in Immunology, 2021)
The accumulation of myeloid-derived suppressor cells (MDSCs) is one of the major obstacles to achieve an appropriate anti-tumor immune response and successful tumor immunotherapy. MDSCs in tumor-bearing hosts are primarily polymorphonuclear (PMN-MDSCs). However, the mechanisms regulating the development of MDSCs remain poorly understood. In this report, we showed that interferon regulatory factor 4 (IRF4) plays a key role in the development of PMN-MDSCs, but not monocytic MDSCs. IRF4 deficiency caused a significant elevation of PMN-MDSCs and enhanced the suppressive activity of PMN-MDSCs, increasing tumor growth and metastasis in mice. Mechanistic studies showed that c-Myc was up-regulated by the IRF4 protein. Over-expression of c-Myc almost abrogated the effects of IRF4 deletion on PMN-MDSCs development. Importantly, the IRF4 expression level was negatively correlated with the PMN-MDSCs frequency and tumor development but positively correlated with c-Myc expression in clinical cancer patients. In summary, this study demonstrated that IRF4 represents a novel regulator of PMN-MDSCs development in cancer, which may have predictive value for tumor progression.